(untitled) (Research, Society and Development, 2026)
Coronary Artery Disease (CAD) is among the pathologies responsible for high mortality rates in Brazil, associated with a significant increase in cardiovascular risk factors. In this context, the purpose of this integrative literature review is to analyze and compare the factors influencing the appropriate choice between percutaneous coronary intervention (PCI) and coronary artery bypass grafting (CABG) in managing this cardiac condition, considering clinical and anatomical variables and the SYNTAX score. CAD presents a broad spectrum of clinical manifestations, and the therapeutic decision depends on individual patient characteristics, including lesion complexity, age, associated comorbidities, and ventricular function. CABG is the preferred clinical alternative for patients with diffuse disease and complex coronary anatomy, while PCI demonstrates better results in less severe lesions with faster recovery. Given the above, this research adopts an integrative literature review approach, seeking to consolidate evidence from the last five years to understand the criteria used in clinical practice and their implications for health outcomes. This comparative analysis aims to promote a more personalized management of CAD, assisting evidence-based therapeutic choices that optimize results for different patient profiles.